2022
DOI: 10.3389/fcimb.2022.943427
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Composition in Prediabetes and Newly Diagnosed Type 2 Diabetes: A Systematic Review of Observational Studies

Abstract: Evidence of gut microbiota involvement in regulating glucose metabolism and type 2 diabetes mellitus (T2DM) progression is accumulating. The understanding of microbial dysbiosis and specific alterations of gut microbiota composition that occur during the early stages of glucose intolerance, unperturbed by anti-diabetic medications, is especially essential. Hence, this systematic review was conducted to summarise the existing evidence related to microbiota composition and diversity in individuals with prediabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 68 publications
(406 reference statements)
3
33
0
Order By: Relevance
“…Many studies showed that the patients with mental and neurological disorders including depressive disorders, schizophrenia, Alzheimer's disease, Parkinson's disease, autism spectrum disorders, attentiondeficit/hyperactivity disorder, and eating disorders also had a lower α-diversity in gut microbiota compared to healthy controls (16,(153)(154)(155)(156)(157). The patients with many chronic diseases such as cardiovascular diseases, cancers, and diabetes mellitus presented a lower α-diversity in gut microbiota, too (158)(159)(160)(161)(162). The abnormal gut microbiota could impair brain function through microbiota-gut-brain axis, making the host more susceptible to the above diseases (6)(7)(8)(9)163).…”
Section: The Industrialization Of Gut Microbiota and Increase Of Dise...mentioning
confidence: 99%
“…Many studies showed that the patients with mental and neurological disorders including depressive disorders, schizophrenia, Alzheimer's disease, Parkinson's disease, autism spectrum disorders, attentiondeficit/hyperactivity disorder, and eating disorders also had a lower α-diversity in gut microbiota compared to healthy controls (16,(153)(154)(155)(156)(157). The patients with many chronic diseases such as cardiovascular diseases, cancers, and diabetes mellitus presented a lower α-diversity in gut microbiota, too (158)(159)(160)(161)(162). The abnormal gut microbiota could impair brain function through microbiota-gut-brain axis, making the host more susceptible to the above diseases (6)(7)(8)(9)163).…”
Section: The Industrialization Of Gut Microbiota and Increase Of Dise...mentioning
confidence: 99%
“…When regarding IBD, the enrichment of adhesive bacteria (involving Veillonella ) increases Th17 cell activation and luminal secretory IgA ( Chen et al., 2020a ; Gonzalez-Soltero et al., 2020 ). In periodontitis-associated type 2 diabetes (T2D), Streptococcus and Veillonella are dominant in the symbiosis network, and microbial shifts may contribute to systemic inflammation and metabolic dysfunction ( Li et al., 2020 ; Letchumanan et al., 2022 ).…”
Section: Mechanisms Of Oral Microbiome Affecting Intestinal Microbiotamentioning
confidence: 99%
“…12 Systematic reviews have associated changes in the gut microbiome with insulin resistance, prediabetes and type 2 diabetes, with some evaluations of probiotics demonstrating improvements in glycaemic control. [13][14][15] These associations are variable, however, and this approach remains in the arena of research. Further study will be needed in this area before targeted modulation of the gut microbiome joins the evidence-based interventions for managing the diabetes continuum that are described later in this article.…”
Section: Clinical Relevance Of the Diabetes Continuum Glycaemic Controlmentioning
confidence: 99%